Spearmint (Mentha spicata L.) leaves essential oil: Comparative compositional and biological attributes as a function of different agroclimatic regions - Saba, Iram; Anwar, Farooq; Ahmad, Naveed; Iqbal, Munawar; Abbas, Ali; Iqbal, Shahid; Nazir, Arif; Al-Mijalli, Samiah H. (Elsevier, 2024)
In the current work, the biological potential of spearmint leaves essential oil (EO), including its antioxidant, antibacterial, and hemolytic properties, are described together with its chemical composition. The spearmint leaves were gathered in Punjab, Pakistan's hilly, dry, irrigated, and drought-stricken agroclimatic zones. From examined leaves from various locales, the hydro-distillation process produced an EO yield that ranged from 0.41 to 0.76. In recovered EOs, GCMS compositional analysis identified 31 components, with carvone (27.4–47.2), menthone (1.0–23.9), menthol (3.0–14.5), limonene (2.4–93), and 1,8-cineol (0.6–8.5) being the predominant constituents. The investigated oils displayed high levels of total phenolics (30.9–34.3 g GAE/100g), flavonoids (4.6–10.1 g CE/100g), and DPPH radical scavenging capacity (12.5–17.1 g mL−1) as well as linoleic acid peroxidation inhibition (57.1–62.6). Against particular types of bacteria and fungus, the studied EO demonstrated considerable antibacterial activity (AMA). EO extracted from a sample of a location under drought stress (Layyah) shown greater AMA, while EO from hilly regions (Murree) displayed higher antioxidant potential, total phenolics (TP), flavonoids (TF), and hemolytic activity (HA). This study recommends the use of spearmint leaves as an effective natural antioxidant and antibacterial ingredient in the development of nutra-pharmaceutical products and dietary supplements. © 2023 Elsevier Ltd